Conformity in the collective: differences in hunger affect individual and group behavior in a shoaling fish. (3rd April 2019) - Wilson, Alexander D M; Burns, Alicia L J; Crosato, Emanuele; Lizier, Joseph; Prokopenko, Mikhail; Schaerf, Timothy M; Ward, Ashley J W
Abstract: Animal groups are often composed of individuals that vary according to behavioral, morphological, and internal state parameters. Understanding the importance of such individual-level heterogeneity to the establishment and maintenance of coherent group responses is of fundamental interest in collective behavior. We examined the influence of hunger on the individual and collective behavior of groups of shoaling fish, x-ray tetras ( Pristella maxillaris ). Fish were assigned to one of two nutritional states, satiated or hungry, and then allocated to 5 treatments that represented different ratios of satiated to hungry individuals (8 hungry, 8 satiated, 4:4 hungry:satiated, 2:6 hungry:satiated, 6:2 hungry:satiated). Our data show that groups with a greater proportion of hungry fish swam faster and exhibited greater nearest neighbor distances. Within groups, however, there was no difference in the swimming speeds of hungry versus well-fed fish, suggesting that group members conform and adapt their swimming speed according to the overall composition of the group. We also found significant differences in mean group transfer entropy, suggesting stronger patterns of information flow in groups comprising all, or a majority of, hungry individuals. In contrast, we did not observe differences in polarization, a measure of group alignment, within groups across treatments. Taken together these results demonstrate that the nutritional state of animals within social groups impacts both individual and group behavior, and that members of heterogenous groups can adapt their behavior to facilitate coherent collective motion. Abstract : We tested how hunger influenced the swimming behavior of individuals as well as groups of fish. We found that groups dominated by hungry fish swam faster and were often farther apart. Within groups, however, there was no difference in the swimming speeds of hungry versus well-fed fish, suggesting that group members conform their swimming speed to that of the majority in their groups. Hungry fish were also more often at the front of the groups and those groups of hungry fish showed higher information flow between group members.